ANALISIS PENGARUH MODAL KERJA, LIKUIDITAS DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN MELALUI HARGA SAHAM SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN ASURANSI YANG TERDAFTAR DI BEI TAHUN 2019-2022 - Fransiska, Feni; Sari, Lita Permata; Subaida, Ida (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
An insurance company is a crucial entity because it provides protection services to the general public. In this context, the insurance company acts as a service provider, while the public serves both as a resource supplier for the company and as its consumers. This research aims to examine how insurance companies listed on the Indonesia Stock Exchange adjust their strategies in response to market and economic changes and the impact of these adjustments on the company's value, with stock price serving as an intermediary variable. The results of the study show that working capital does not have a significant impact on stock price and company value. Liquidity has a significant effect on stock price but does not impact company value. Profitability has a positive and significant effect on company value but does not significantly influence stock price or company value through stock price. Stock price has a positive and significant effect on company value. In conclusion, profitability and stock price are important factors in determining company value, while working capital and liquidity do not have significant effects.